Chemical signature and antimicrobial activity of Central Portuguese Natural Mineral Waters against selected skin pathogens - Oliveira, AS (2020)
The common therapeutic indications of Portuguese Natural Mineral Waters (NMWs) are primarily for respiratory, rheumatic and muscu- loskeletal systems. However, these NMWs have been increasingly sought for dermatologic purposes. Opposing to what is observed in the major European Thermal Centres, there are few scientific evidences supporting the use of Portuguese NMWs for clinical applications. The aim of this study was to characterize the antimicrobial profile of individual NMWs from the central region of Portugal and correlate the results with their physicochemical characterization. An extensive multivariate analysis (principal component analysis) was also performed to further investigate this possible correlation. Six collection strains representing skin microbiota, namely Staphylococcus aureus, Escher- ichia coli, Corynebacterium amycolatum, Candida albicans, Staphylococcus epidermidis and Cutibac- terium acnes, were analysed, and their antimicrobial profile was determined using Clinical and Laboratory Standards Institute M07-A10, M45-A2, M11-A6 and M27-A3 microdilution methods. Different NMWs presented different antimicrobial profiles against the strains used; the physicochemical composition of NMWs seemed to be correlated with the different susceptibility profiles. Cutibacterium acnes showed a particularly high susceptibility to all NMWs belong- ing sulphurous/bicarbonated/sodic ionic profile, exhibiting microbial reductions up to 65%. However, due to the complex physicochemical composition of each water an overall conclusion regarding the effect of a specific ion on the growth of different microor- ganisms is yet to be known.